(3GdSjGSI aj Yde GdaQGSIs - (3TjN GdQHhI , CHh YHO Gddg eMeO Hf CHj WGdH GdCfUGQj GdUhaj GdOeTbj, TjN GdQHhg (B/ (3TjN MWjf,J (B727 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg QSGdJg eTJedI Ydi eYGbO LeI ef Yde GdaQGSI dCLd GdSjGSI hGdcdGe s
(3BNQgG (B:s
(3JeJ GdbVGjG GdNeSI hGdYTQjf bVjI hGddg CYde GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B94s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGSIs